Materials science and technology :a comprehensive treatment /. Volume 10A, Nuclear materials Part I / edited by R.W. Cahn, P. Haasen, E.J. Kramer; vol.ed. : Brian R. T. Frost - Brian R. T. Frost
Vol. 10A. Nuclear materials Part I. - 1994